The Life Of Preschool Education Yesterday, Today And Tomorrow - G'aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2023)
: This article describes the current state and shortcomings of preschool education, the ongoing reforms on this issue and the focus on preschool children, the reorganization of the preschool education system, more will be devoted to the work to be done in the coming years.